Water availability analysis of Walanae River - Lias, Syamsul Arifin; Assegaf, A; Sakka, Sakka; Paharuddin, Paharuddin; Syamsuddin, E (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2022)
The Walanae Watershed plays an essential role as a water provider for irrigation and industry in the central part of South Sulawesi Province, Indonesia. The Walanae River flows through Enrekang, Soppeng, and Bone Regencies. This paper describes the availability of water in the Walanae watershed. Water discharge of the Walanae river recorded at Tampangeng station from 2000 to 2014 is analyzed using descriptive statistics to obtain a flow duration curve. The calculation results show that the available discharge is quite extensive throughout the year with a range of 16.5 m3.s–1–316 m3.s–1, and an average of 138 m3.s–1. The minimum discharge generally occurs from September to November, while the peak discharge generally occurs in January and July. The results show that water availability for 9, 10, 11 months, and all years are: 92.2 m3.s–1, 83.4 m3.s–1, 66.3 m3.s–1, and 15.8 m3.s–1, respectively.